Study on architecture and control technology of multi-stack fuel cell system for rail transit - LIU Baibo; ZHANG Han; ZHANG Bo; MA Tiancai (机车电传动)
To satisfy the high-power application demands of rail transit vehicles, an architecture and control method of a multi-stack fuel cell system specifically designed for rail transit was proposed. Firstly, the topology of the multi-stack system was designed based on the definition of the multi-stack fuel cell system, including the overall system, the single-stack system, the thermal management system and the electrical system. Then, the control system of the multi-stack system was designed, covering network topology, control flow, and power allocation strategy. Finally, a prototype of a 350 kW multi-stack fuel cell system was developed and validated on a certain type of shunting locomotive manufactured by CRRC. The results show that the proposed solution can fulfill the high-power demand of daily work for shunting locomotives, with the rated working point efficiency of the prototype reaching 42.1%.